System and Mechanism Development in Area-Based Collaborative Research Management of Rajamangala University of Technology Srivijaya - Na Ranong, Sutkanung; Songrak, Apirak; Piyang, Tuanjai (Area Based Development Research Journal, 2020)
This article presents the research management system and mechanism of Rajamangala University of Technology Srivijaya developing as an Engagement University. Description of the system covers all stages of the research process management -- upstream, midstream, and downstream. The important management tools include logical framework analysis, stakeholder analysis, and impact assessment. Notably, a support system is provided for smooth operations, which include mentoring system, researcher’s competency development, and follow-up session or periodic progress report. The university ensures availability of co-working spaces to connect researchers and users. Most important of all, the university is rather adaptive with policy management, as seen in adjustment in regulations to serve research work conduct. The results of research management system in the year 2017-2018 reveal the research grants totaling 8.2 million baht for 22 research projects, with 100% of sub-research project completion. The research results have been sustainably transferred to communities in the Palian basin for authentic use. Academic achievements include 8 research article publications, 5 patent submissions, 68 area-based researchers from 10 faculties in 3 university areas -- Songkhla, Trang and Nakhon Si Thammarat. In summary, the management of area-based research mechanisms successfully develops researcher’s skills required to advance the university towards an institution for social engagement.